Seawater carbonate chemistry and critical thermal minimum/maximum and oxygen consumption rates of fish - Gimenez, Eloísa M; Vanella, Fabian A; Wolinski, Laura I; Torres, Rodrigo; Lattuca, María E (PANGAEA, 2025)
This study seeks to explore the combined effects of warming and acidification on the thermal and metabolic responses of Patagonotothen tessellata and Harpagifer bispinis, two sympatric notothenioid fish from the Beagle Channel. Juveniles were exposed to present-day and near-future summer temperatures (∼10 and 13 °C) and pCO2 levels (∼500 and 1300 μatm) in a full factorial design. Their critical thermal minimum/maximum (CTmin/CTmax) were assessed and their partial thermal tolerance polygons were estimated. Oxygen consumption rates allowed us to calculate fish' aerobic scope (AS) as the difference between the standard and maximum metabolic rates (SMR and MMR). This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were extracted from tables in the related paper (see Related to) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-04-23.
Keywords: Animalia; Chordata; Coast and continental shelf; Containers and aquaria (20-1000 L or < 1 m**2); Harpagifer bispinis; Laboratory experiment; Nekton; Other studied parameter or process; Patagonotothen tessellata; Pelagos; Respiration; Single species; South Atlantic; Temperate; Temperature